Student decisions in choosing hospitality study program at IPB International - Ni Putu Ayuning Permatasari; I Wayan Eka Mahendra; Moch Nur Efendi; I Nengah Dasi Astawa (Institute of Computer Science (IOCS), 2023)
This study aims to determine how much influence the college image, job opportunities, and education costs have on the decision to choose a hospitality study program and strategies that can be suggested to support the decision to choose a hospitality study program at IPB International. The population in this study were students of the IPB International Hospitality Diploma III Study Program batch 2020, 2021, 2022. The sample was determined using simple random sampling technique, with a total of 213 respondents. The data collection technique of this study used interviews, documentation, and questionnaires. analyzed using multiple linear regression analysis. University image, job opportunities, and tuition fees together have a positive and significant effect on the decision making of new students in choosing a hospitality study program at IPB International. The influence of each variable on student decisions in choosing the Diploma III Hospitality study program is the highest is the image of the university by 61.2%, job opportunities by 43.6% and the lowest is the cost of education by 23.4%. Judging from the magnitude of the influence of each variable, the recommended strategy is to maintain a good image by increasing the accreditation of study programs, and maintaining the quality of lecturers, lecture programs, and facilities. This research can provide information and knowledge about the influence of college image, job opportunities, and education costs on student decision making in choosing a hospitality study program at IPB International.